Understanding Li dendrites in solid-state batteries - Melvin, D (2024)
As the requirements placed on rechargeable batteries continue to expand, next-generation technologies beyond today’s Li-ion cells are being increasingly sought. Solid-state designs using lithium metal anodes may provide a leap in energy density, but their charging currents have been limited by the formation of Li dendrites which lead to catastrophic cell failure. In this thesis, an examination is made into both the origin of Li dendrites as well as the influence of the solid electrolyte’s microstructure and mechanical properties.